Efeito do processamento sobre a composição de compostos fenólicos presentes no suco de cajú - Sá, Nádia Maria dos Santos Matos (2012)
In the fruit processing industry, the cashew pulp is used during the offseason to obtain various products such as cashew juice. The increasingly frequent consumption of processed foods arouses interest in the products that are being consumed and the influence of processing is still poorly studied. Hence the importance of verifying the influence of processing on the beneficial compounds present in cashew apple juice. This study aimed to quantify the amount of phenolics and evaluate the in vitro antioxidant activity by ABTS method in processed cashew juice. The juice was obtained from the peduncle of the cashew clone CCP 76 in an expeller type press. The thermal treatment was carried out in a bench scale at five temperature (55, 65, 75, 85 and 95 ° C) and four times (5, 15, 30 and 60 minutes). Immediately after the heat treatment, the samples were cooled in an ice bath and stored in plastic bottles for further analysis. The phenolics were identified as 1-O-trans-cinnamoyl--D-glucopyranose, cinnamic acid and isomers. With regard to antioxidant activity, the results using the ABTS radical, had TEAC values of 7.11 ± 0.08 for the aqueous extract and 6.59 ± 0.02 for the methanol extract (mM Trolox / mL of juice). From these results we can conclude that still of phenolic concentration changes during processing, there was no change on cashew juice antioxidant activity related to thermal treatment.